Thermal analysis of FeCoCu pre-alloyed powders used for diamond tools - Delong Xie; Leyin Xiao; Feng Lin; Xiaoyi Pan; Yu Su; Xiaohu Fang; Haiqing Qin; Chao Chen (Сверхтвердые материалы, 2018)
By simulating the pressureless sintering process, the thermal effects of FeCoCu pre-alloyed powders have been investigated. According to the notions of the Kissinger method, the activation energies in the expansion-shrinkage conversion stage are analyzed. Results show that with Fe content increasing, the specimens’ specific heat capacity values present the increasing trend. The 25 %Fe–15 %Co–60 %Cu specimens have negative enthalpy value at 10 and 20°C/min heating rate but positive values at 30 °С/min. For the specimens with lower Cu content, the enthalpies are always positive. It is established that both the specific heat capacity and enthalpy are larger when at higher heating rates. The activation energy of the 65 %Fe–15 %Co–20 %Cu specimens is 10 times higher than that of the 25 %Fe–15 %Co–60 %Cu specimens and the 45 %Fe–15 %Co–40 %Cu specimens. При моделюванні процесу спікання без тиску досліджено термічні ефекти в попередньо легованих порошках FeCoCu. З використанням методу Кіссінджера проаналізовано енергію активації на стадії розширення–усадка. Результати показують, що при збільшенні вмісту Fe значення питомої теплоємності демонструють тенденцію до зростання. Зразки 25 %Fe–15 %Co–60 %Cu мають негативні значення ентальпії при швидкості нагріву 10 ° і 20 °С/хв, але позитивні при 30 °С/хв. Для зразків з меншим вмістом Cu ентальпія завжди позитивна. Встановлено, що питома теплоємність і ентальпія більші при більш високіх швидкостях нагрівання. Енергія активації зразків 65 %Fe–15 %Co–20 %Cu у 10 разів вища, ніж зразків 25 %Fe–15 %Co–60 %Cu і 45 %Fe–15 %Co–40 %Cu. При моделировании процесса спекания без приложения давления исследованы термические эффекты в предварительно легированных порошках FeCoCu. С использованием метода Киссинджера проанализирована энергия активации на стадии расширение–усадка. Результаты показывают, что с увеличением содержания железа значения удельной теплоемкости образцов демонстрируют тенденцию к повышению. Образцы 25 %Fe–15 %Co–60 %Cu имеют отрицательные значения энтальпии при скорости нагрева 10 и 20 °С/мин, но положительные при 30 °С/мин. Для образцов с меньшим содержанием Cu энтальпия всегда положительна. Установлено, что удельная теплоемкость и энтальпия больше при более высоких скоростях нагрева. Энергия активации образцов 65 %Fe–15 %Co–20 %Cu в 10 раз выше, чем образцов 25 %Fe–15 %Co–60 %Cu и 45 %Fe–15 %Co–40 %Cu.